Implementation of LKPD Based on the PjBL Learning Model of Ethnoscience Integration: A Systematic Literature Review - Hermanto Hermanto; Moch. Haikal Moch. Haikal; Linda Tri Antika; Maimun Sumo (FKIP - Universitas Riau, 2026)
The integration of ethnoscience into Project Based Learning (PjBL) provides opportunities to connect scientific concepts with local knowledge and cultural contexts. However, research on ethnoscience integrated PjBL based Student Worksheets (LKPD) remains fragmented and insufficiently mapped. This study aims to systematically review research trends, dominant themes, research gaps, and emerging directions in this field. A Systematic Literature Review was conducted using the PRISMA framework. From 200 identified records, 20 studies published between 2021 and 2026 met the eligibility criteria. Publications were concentrated in 2024–2025, with 13 studies (65%) published during this period, including 9 studies (45%) in 2025. Bibliometric analysis using VOSviewer revealed increasing connections between ethnoscience, PjBL, STEM/STEAM, scientific literacy, creative thinking, and critical thinking. This pattern indicates a shift from using ethnoscience primarily to contextualize scientific concepts toward integrating local knowledge with interdisciplinary and competency oriented learning. However, ethnoscience integrated PjBL based LKPD remains less prominent than broader pedagogical themes, indicating a gap in instructional materials that systematically connect local contexts, project activities, and learning outcomes. Future research should focus on developing and evaluating such LKPD across diverse science topics and educational contexts.